ANALISIS KINERJA KEUANGAN PADA PT BANK SYARIAH INDONESIA - Umiyati, Umiyati; Muthahari, Alif; Indayatun, Ratna (Gapenas Publisher, 2024)
The analysis of financial performance plays a critical role in determining the success and sustainability of a financial institution, including Bank Syariah Indonesia. As a financial institution operating based on Islamic principles, Bank Syariah Indonesia faces unique challenges, both in terms of compliance with Islamic law and competition with conventional banks. The objective of this study is to examine the financial performance of PT Bank Syariah Indonesia (BSI) for the 2021–2023 period. The research employs a quantitative descriptive method. All indicators show positive trends, with an increase in ROA (Return on Assets) and a decrease in BOPO (Operational Costs to Operational Revenue), reflecting good efficiency and profitability. ROA and BOPO fall within the